1997
DOI: 10.1093/oxfordjournals.aje.a009127
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cancer and Exposure to Gasoline Vapors

Abstract: Until the introduction of self-service around 1970, service station workers in the Nordic countries were exposed to gasoline vapors. Based on measurements reported in the literature, the 8-hour time-weighted average benzene exposure was estimated to be in the range of 0.5-1 mg/m3. We studied the cancer incidence in a cohort of 19,000 service station workers from Denmark, Norway, Sweden, and Finland. They were identified from the 1970 censuses and followed through 20 years, where 1,300 incident cancers were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 0 publications
3
64
2
3
Order By: Relevance
“…An excess risk of nasal cancer in workers exposed to benzene in gasoline vapours has been reported [78], but the present study did not suggest such associations. Increased risk of nasal cancer has also been found to be associated with exposures to employment in the nickel process industry [79].…”
Section: Cancer Of the Nose And Nasal Sinusescontrasting
confidence: 99%
“…An excess risk of nasal cancer in workers exposed to benzene in gasoline vapours has been reported [78], but the present study did not suggest such associations. Increased risk of nasal cancer has also been found to be associated with exposures to employment in the nickel process industry [79].…”
Section: Cancer Of the Nose And Nasal Sinusescontrasting
confidence: 99%
“…Several studies yielded relative risk estimates close to 1.0 among persons exposed to diesel exhaust [170][171][172][173][174] or gasoline vapors, 29,175,176 and there is no epidemiologic evidence supporting a causal relationship between working in the petroleum industry and risk of developing NHL. Relative risks have been near unity in petroleum worker cohort studies in California, 177,178 Texas, [179][180][181] Louisiana, 182,183 US, [184][185][186] Canada 187,188 and Australia.…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 99%
“…Epidemiologic evidence does not support a causal relationship between benzene exposure and multiple myeloma, as cohort and case-control studies have not indicated consistently elevated relative risks 47,[130][131][132][133][134][135][136][137] and there is no evidence of a significant exposure-response pattern. 89,138,139 Of 5 multiple myeloma deaths that occurred in the updated report of a cohort of rubber hydrochloride workers, 4 were in the lowest exposure quartile.…”
Section: Organic Solventsmentioning
confidence: 99%